2020
DOI: 10.3389/fpls.2020.00979
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate Solubilizing Rhizobacteria Could Have a Stronger Influence on Wheat Root Traits and Aboveground Physiology Than Rhizosphere P Solubilization

Abstract: Limited P availability in several agricultural areas is one of the key challenges facing current agriculture. Exploiting P-solubilizing bacteria (PSB) has been an emerging bio-solution for a higher rhizosphere P-availability, meanwhile the above-and below-ground interactions that PSB would trigger remain unclear over plant growing stages. We hypothesized that PSB effects on plant growth may be greater on root traits that positively links with aboveground physiology more than the commonly believed rhizosphere P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
68
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 100 publications
(77 citation statements)
references
References 91 publications
8
68
0
1
Order By: Relevance
“…Ketersediaan P yang terbatas di beberapa wilayah pertanian merupakan salah satu tantangan utama yang dihadapi pertanian saat ini. Memanfaatkan bakteri pelarut P (PSB) telah menjadi solusi yang muncul untuk ketersediaan P rhizosfer yang lebih tinggi (Elhaissoufi et al, 2020). Fosfor (P) adalah salah satu unsur penting yang diperlukan untuk pertumbuhan dan perkembangan tanaman.…”
Section: Pendahuluanunclassified
“…Ketersediaan P yang terbatas di beberapa wilayah pertanian merupakan salah satu tantangan utama yang dihadapi pertanian saat ini. Memanfaatkan bakteri pelarut P (PSB) telah menjadi solusi yang muncul untuk ketersediaan P rhizosfer yang lebih tinggi (Elhaissoufi et al, 2020). Fosfor (P) adalah salah satu unsur penting yang diperlukan untuk pertumbuhan dan perkembangan tanaman.…”
Section: Pendahuluanunclassified
“…Altogether, nodule formation, nodule functioning, and the energy costs of BNF in legumes strongly depend on the P status in plants and nodule tissues, and inadequate P status will reduce potential BNF contribution to N uptake (Bargaz et al, 2018). Given all of the knowledge regarding the key role of P in enhancing plant growth either by boosting the size of the root system (i.e., root hair density, lateral root growth, root surface area, and nodulation) or by stimulating the BNF process, soil PSM represents a promising strategy that could be adopted to increase plant-accessible forms of P to maintain soil health, fertility and agricultural sustainability (Wani et al, 2007;Qureshi et al, 2011;Bargaz et al, 2018;Elhaissoufi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The discovery of phosphate solubilizing bacteria has led to its use in agriculture as a potential biofertilizer. For example, it has been reported that phosphate solubilizing rhizobacteria strongly influences wheat root traits and aboveground physiology (Elhaissoufi et al, 2020 ). Although seed priming is facing many challenges related to the conservation of bioformulation, storage, and difficulties in upscaling management.…”
Section: Introductionmentioning
confidence: 99%